The role of the gut microbiota and fecal microbiota transplantation in neuroimmune diseases - Wu, Nan; Li, Xizhi; Ma, He; Zhang, Xue; Liu, Bin; Wang, Yuan; Zheng, Qi; Fan, Xueli (Frontiers in Neurology, 2023)
The gut microbiota plays a key role in the function of the host immune system and neuroimmune diseases. Alterations in the composition of the gut microbiota can lead to pathology and altered formation of microbiota-derived components and metabolites. A series of neuroimmune diseases, such as myasthenia gravis (MG), multiple sclerosis (MS), neuromyelitis optica spectrum disorders (NMOSDs), Guillain–Barré syndrome (GBS), and autoimmune encephalitis (AIE), are associated with changes in the gut microbiota. Microecological therapy by improving the gut microbiota is expected to be an effective measure for treating and preventing some neuroimmune diseases. This article reviews the research progress related to the roles of gut microbiota and fecal microbiota transplantation (FMT) in neuroimmune diseases.